2011
DOI: 10.1007/s12185-011-0922-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the humeral head

Abstract: A 20-year-old man with a 5-year history of acute lymphoblastic leukemia (ALL) was admitted to our hospital for severe pains in his bilateral groin and right shoulder. He had experienced these pains for 16 months. He underwent allogeneic stem cell transplantation in his second complete remission 13 months prior to hospitalization. He had received corticosteroid therapy both for ALL and for graft versus host disease for a long period (more than 13 months in total), and the total dose of corticosteroids exceeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The necrotic area is still visible on imaging scans, although the degree of bone marrow oedema has been reduced substantially. This result, however, is to be expected if we consider the slow healing capacity of the humeral head; indeed, numerous studies have demonstrated the late onset of AVN up to two or more years after relevant trauma or causes [1,5,12,19,22,28,34].…”
Section: Discussionmentioning
confidence: 99%
“…The necrotic area is still visible on imaging scans, although the degree of bone marrow oedema has been reduced substantially. This result, however, is to be expected if we consider the slow healing capacity of the humeral head; indeed, numerous studies have demonstrated the late onset of AVN up to two or more years after relevant trauma or causes [1,5,12,19,22,28,34].…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism relates to alterations in lipocytes, leading to microemboli in the blood supply to the humerus and subsequent ischemia 43 . Another mechanism suggests that adipocyte hypertrophy and hyperplasia of the bone marrow compartment of convex joints results in elevated intraosseous pressure by blocking venous outflow causing ischemia to the bone 6,31,37,38,44 . A third theory suggests that disruption to vascular endothelial cells results in stasis and a subsequent increase in intraosseous pressure leading to eventual ischemia 45 .…”
Section: Etiology Of Humeral Head Avnmentioning
confidence: 99%
“…Patients receiving chronic high-dose corticosteroids are well known to be at increased risk for AVN 1,4,6,20,22,29,30,31,32,33,34,35,36,37,38,39,40 . The prevalence of AVN at any location with corticosteroid use ranges from 21% to 37% 41 .…”
Section: Etiology Of Humeral Head Avnmentioning
confidence: 99%
“…The humeral head is the second most common site for osteonecrosis after the femoral head. Osteonecrosis is associated with corticosteroid use, trauma, sickle cell disease, alcoholism, dysbarism (caisson disease), Gauchers disease and other systemic conditions [9, 12].…”
Section: Introductionmentioning
confidence: 99%